“Densidades del cultivo de sandía (citrullus vulgaris) variedad peacock wr60 en la localidad de bello horizonte provincia de San Martín” - Santillán Olivera, Miguel (2003)
The work present was developed, in order to determining the density of seeding of the single variety Peacock WR 60; in the town of Bello Horizonte, District of the Banda of Shilcayo, Country and Region of San Martín, Area of lite tropical dry forest (Bs-T), with a pluvial precipitation of 1 200 mm/año; it was installed under a design block complete randomizado, with 4 treatment and 4 repetitions. lt was evaluated the growth of the shaft, number of fruits, yield of the fruit and the relationship 1 benefit cost of the cultivation. According to the results, the watermelon variety Peacock WR 60, with the distancing of 4 x 4 m (T1), it reached bigger longitude of the shaft (20.44 m) and the but high yield with a production of 36 562 Kg/ha, likewise an utility of was obtained SI. 6 862.56 new suns what represents a relationship of 2.68, with the distancing 5 x 5 m (T 3) it reached the biggest number (5.20) of fruits for plant. The local variety (Picurina) with distancing of 4 x 4 m their yield was of 24 046.00 Kg/ha.